Book Review: Ioan-Aurel Pop, “Hunedoreştii. O istorie europeană” [“The Hunedoreşti Family. A European History”], Cluj-Napoca, Editura Şcoala Ardeleană, 2020, 428 p. - COSTEA, Ionuț (Studia Universitatis Babeș-Bolyai Historia, 2022)
The book written by historian Ioan-Aurel Pop not only offers a comprehensive perspective on the destiny of a family with a significant resonance within the history of the medieval kingdom of Hungary and its province of Transylvania, but it also illustrates the political, social, confessional and cultural evolutions from this area of central and south-eastern Europe in the 15th and 16th centuries. Thus, the book is at the boundary between a historical monograph dedicated to the Hunedoreşti family and a synthesis of the history of the Transylvanian Romanians from the Middle Ages. In fact, the history of the Romanians from Transylvania during the Middle Ages represents the research field preferred by the aforementioned historian, a theme that accompanied a prodigious academic career.